Kecernaan Bahan Kering dan Bahan Organik Jerami Padi Varietas Pandanwangi secara In–Vitro yang Diberi Pupuk Organik dan Anorganik - Satria Andy Prabowo; Muhamad Bata; Sri Rahayu (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. The research aims to examine the influence of organic and inorganic fertilization of dry matter digestibility (DMD) and organic matter digestibility (OMD) of Pandanwangi. The reaserch was conducted from 27 September to 28 December 2019, at the Laboratory of Animal Nutrition and Forage, Faculty of Animal Husbandry, Jendral Soedirman University, Purwokerto. Materials and methods. The material used in this research was Pandanwangi rice straws which are planted in organic and inorganic fields. The straw stalks were cut at 10 cm away from the land surface and taken randomly out from 20 spots in a field, which then dried using oven. The research method was in-vitro experiment with independent t-test research design. The rumen fluid used for measuring the dry and organic matters digestibility was taken from 3 cows which come from Bantarwuni slaughterhouse. Results. Based on the T-test analysis, it showed that the DMD and OMD of the Pandanwangi straws with organic fertilization is relatively similar (P > 0.05) to the DMD and OMD resulted in the straws with inorganic fertilization. Conclusion. Pandanwangi rice straw resulting from organic and inorganic fertilization has relatively the same of DMD and OMD.